A compact wideband Wilkinson Power Divider topology for arbitrary N-Way outputs - Shrawan K. Patel; Rusan Kumar Barik; Niraj Kumar Dewangan; Shweta Kumari; Mrinal K. Mandal (PLoS ONE, 2026)
This work presents a compact Wilkinson power divider (WPD) topology capable of realizing arbitrary 1 × N equal power divisions without requiring crossovers or unrealizable high-impedance lines. The design combines both equal and unequal power division stages, enabling flexibility for even and odd numbers of outputs. Power divider units with 1:2 and 1:3 ratios are used as the basis for constructing higher-order N-output WPDs. Miniaturization is achieved through tapered-line impedance transformers, limiting the maximum line impedance to 103 Ω within fabrication constraints. A two-stage 1 × 3 divider is designed, fabricated, and tested at 2.4 GHz on a microstrip platform. The prototype demonstrates an 85% effective bandwidth with amplitude imbalance within ±0.2 dB, and phase imbalance less than ±2.5°. Compared to conventional topologies, the present approach achieves up to 58% size reduction while maintaining wideband performance. This work is highly suitable for M × N high-performance, efficient, reliable, and scalable beamforming network architecture. This work supports SDG 9 Industry Innovation and Infrastructure by enabling compact, scalable, and high-efficiency microwave components for advanced communication and infrastructure systems.